PRAKTIK MANAJEMEN RANTAI PASOKAN DI INDUSTRI KELAPA SAWIT DI INDONESIA - Wiwik Rachmarwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The palm oil industry has become an important industry for the Indonesian economy. The palm oil industry has the potential to generate significant economic and social development in Indonesia. Palm oil is the second most successful agricultural product in Indonesia after rice, and is the largest agricultural export. The industry consists of interrelated business activities that produce various palm oil products. Therefore, in order for these firms to operate efficiently along their supply chain, they need a better approach in their supply chain management. Therefore, this paper aims to propose a research framework to investigate supply chain practices in the palm oil industry. This research framework needs to be tested using the data of palm oil industry companies in Indonesia, because this framework is slightly different from other industries